Internet marketing : building advantage in the networked economy - Rafi A. Mohammed (McGraw-Hill, 2004)
Presents a framework to help students and practitioners understand how to think about and implement effective Internet marketing programs. This book focuses on using marketing levers to vary the level of intensity that the consumer has, to build a relationship with the customer through awareness, exploration/expansion, commitment, and dissolution